Stare Decisis and the Electoral Connection: Do Retention Systems Affect Judges' Deference to Precedent?. (June 2020) - Miller, Michael G.; Tuma, Michelle D.
Using data from nearly 5, 000 votes cast by more than 400 judges in courts of last resort from all 50 states, we investigate whether there is a relationship between a state's judicial retention method and the likelihood that a judge votes to join a precedent-overturning majority. We find that relative to judges retained by institutions such as judicial commissions or state legislatures, those retained via either partisan or retention elections are significantly more likely to join majorities that overturn precedent. Most of this effect is due to behavior in high-profile cases that garner media attention. We find little evidence that an impending election moderates these effects. Finally, we find no evidence that judges retained via nonpartisan elections treat precedent differently than their institutionally retained colleagues.